Mettl3 deficiency leads to impaired insulin secretion via regulating Ire1a of mature β-cells in mice - Xu Zhang; Aijing Shan; Jie Chen; Yanan Cao; Xiuli Jiang (Scientific Reports)
Abstract The modification of N6-methyladenosine (m6A) influences the translation and stability of transcripts, allowing for the coordination of gene regulation during cell state maintenance and transition. Deregulation of components in the m6A regulatory network is associated with glucose homeostasis and development of diabetes. In this study, we investigated the functional role of Mettl3, which is the key component of the m6A methyltransferase complex, in regulating β-cell identity and function in two pancreatic β-cell-specific Mettl3 knockout mouse models. The glucose metabolic phenotype, β-cell proliferation, islet architecture and insulin secretion were analyzed in vivo. We next analyzed the expression levels of genes associated with endoplasmic reticulum (ER) stress in the Mettl3 ablated islets. MeRIP-qPCR was applied to detect the m6A modification enrichment of Ire1α mRNA. Adenovirus-mediated Mettl3 infection was performed on islets to explore the effect of Mettl3 overexpression on ER stress and insulin secretion. Our results showed that Mettl3 deficiency led to loss of β-cell identity and impaired insulin secretion in mice. Depletion of Mettl3 verified the m6A modification in Ire1α and consequently induced ER stress in islet cells. Mettl3 overexpression in islets could alleviate ER stress and improve the insulin secretion capacity. Our findings demonstrated that Mettl3 was an important regulator of ER stress and insulin secretion in mouse pancreatic β-cells.